External Environment and Individual Confidence Influence on Purchase Decisions - Rahmatullah, Rahmatullah; Anwar, Nurul Afiah; Azisah Alisyahbana, Andi Naila Quin; Isma, Andi (Pinisi Business Administration Review, 2022)
This study aims to determine the influence of the individual's external environment and self-confidence on student purchasing decisions. This type of research is quantitative research using a descriptive correlation approach with data collection techniques through questionnaires. The data analysis technique used is multiple regression analysis with partial test (t test), simultaneous (F test), coefficient of determination test (R2), and partial determination coefficient test (r2). The results showed that the individual's external environment and self-confidence simultaneously had a significant effect on students' purchasing decisions. Partially, the individual external environment has a significant effect on purchasing decisions, as well as the self-confidence variable partially has a significant effect on purchasing decisions